The International Criminal Court and Africa: a legal alternative to implementing international criminal justice - Mensah, Cocou Marius; Bukuru, Jean Baptiste (The ICC at 25: Lessons Learnt, 2025)
The International Criminal Court (ICC) has been criticised for its perceived focus on Africa in addressing war crimes, genocide, and crimes against humanity. This chapter contends that ensuring justice for victims in Africa is crucial, necessitating a complementary relationship between the ICC and regional justice bodies. The chapter examines the regional initiatives established by the African Union and its Member States to provide a legal alternative, supplementing the ICC’s efforts. By prosecuting individuals accused of international crimes in regional, national, or hybrid tribunals, such as the African Extraordinary Chambers in Senegal, these initiatives aim to deliver justice to victims while addressing concerns of bias. This paper advocates for a collaborative approach between the ICC and regional mechanisms to combat impunity and promote accountability for grave human rights violations.Keywords: International Criminal Justice, International Crimes, International Criminal Court, Rome Statute, African Union, African RegionalTribunals